The Meaning of Economic Empowerment Activities in Earthquake-Affected Village - Djuhardi, Lidia; Mahanani, Estu; Malays, Essy; Gassing, Syarifuddin S.; Ekowati, Sri (Global Writing Academica Researching & Publishing, 2024)
The earthquake disaster in Cianjur regency, West Java, Indonesia, measuring 5.6 on the Richter scale on November 21, 2022, caused massive damage. Therefore, the Community Self-Reliance Activity (CSRA) of the University of Persada Indonesia YAI is conducting economic empowerment activities as a strategy to recover the condition of rural communities affected by the earthquake.This research aims to describe how village communities interpret the activities conducted by the Community Self-Reliance Activity (CSRA) of the University of Persada Indonesia YAI to strengthen village communities affected by the earthquake disaster.This research uses the paradigm of interpretive phenomenology with a qualitative descriptive approach. The result of this study is that informants indicated positive behaviors in the course of activities. Informants interpreted economic empowerment as activities that benefit, educate, entertain, and motivate village communities affected by the earthquake to wake up from the downturn.